Fatigue of wire+arc additive manufactured Ti-6Al-4V in presence of process-induced porosity defects. (September 2021) - Akgun, Emre; Zhang, Xiang; Biswal, Romali; Zhang, Yanhui; Doré, Matthew
Highlights: Wide range of crack initiating pores (20–400 μm) was studied under CA axial loading. Scatter of fatigue life data is mainly due to pore location, not the pore size. Pores larger than 85 μm behave like notches instead of the usual crack assumption. Linear S-N curve fitting possible after categorising data based on failure source. Notch stress approach was shown within 95% prediction interval of the test data. Abstract: Currently, additive manufactured titanium alloy Ti-6Al-4V predominantly fails from process-induced defects, when subjected to cyclic loading in the polished condition. These defects not only lead to premature failure, but also contribute to the significant dispersion of fatigue life commonly seen in metal additive manufacturing. In this work, we have studied the source of dispersion and the influence of pore size on fatigue life using samples from the standard processing route and samples with intentionally introduced porosity defects. According to the fracture surface study, contrary to the common belief, the source of dispersion is primarily the pore location, e.g. surface or embedded pore, rather than the pore size. In the case of embedded pores as the failure source, a threshold pore size of approximately 85 μm was observed, below which the wrought level fatigue performance was achieved. For surface pores above the threshold size, fatigue life was reduced by two orders of magnitude, but remained unchanged, even though crack initiating pore size increased roughly by a factor of four. This experimental observation was supported by local elastic stress analysis, which indicated that pores above a certain size could behave like micro-notches suggesting the popular Kitagawa-Takahashi diagrams should be presented with a horizontal asymptote for this alloy.